Posted by
**Margie** on
.

Solve the system of equations using the Addition method.

2a + 3b = -1

3a + 5b = -2

The addition method tells you to find common multiples of a coefficient, then add the equations together to eliminate a variable.

If you multiply the first equation by 3 and the second by -2 you have

2a + 3b = -1

3a + 5b = -2

becomes

3 (2a + 3b = -1)

-2(3a + 5b = -2)

which is

6a + 9b = -3

-6a-10b = 4

Now add together to get

-b=1 or b=-1

Now substitute into either equation and solve for a.